YTHDF1 Regulates Tumorigenicity and Cancer Stem Cell-Like Activity in Human Colorectal Carcinoma - Bai, Yang; Yang, Chunxing; Wu, Runliu; Huang, Lihua; Song, Shenlei; Li, Wanwan; Yan, Peichen; Lin, Changwei; Li, Daojiang; Zhang, Yi (Frontiers in Oncology, 2019)
YTH N6-methyladenosine(m6A) RNA binding protein 1 (YTHDF1) is a core factor in RNA methylation modification. Recent studies have shown that m6A is closely related to multiple tumors, thus YTHDF1 may also play a role in tumorigenesis. This study, aimed to explore the role of YTHDF1 in the colorectal cancer (CRC) . In this study, we identified YTHDF1 as being highly expressed at the mRNA and protein levels in TCGA, GEO CRC and primary CRC. Furthermore, the YTHDF1 gene copy number was positively correlated with YTHDF1 mRNA expression in CRC. Knocking down the expression of YTHDF1 significantly inhibited the CRC cell’s tumorigenicity in vitro and murine xenograft tumor growth in vivo. Furthermore, silencing of YTHDF1 inhibited the colonosphere formation ability in vitro. Mechanistically, we found that silencing YTHDF1 significantly inhibited Wnt/β-catenin pathway activity in CRC cells. Together, YTHDF1 is overexpressed in CRC and plays a vital oncogenic role in CRC, and this novel finding may provide a potential therapeutic target for CRC.